Manual drafting for interiors - Cavataio, S. Christine. 4 0 16; 5 (Hoboken, N.J. : John Wiley & Sons, 2012)
This complete learning package begins with an explanation of the drafting tools and their use, and then presents instructions and illustrations that indicate how to complete increasingly more difficult drafting conventions. In addition, readers will learn drawing techniques for indicating various materials, symbols for coordinating related drawings and architectural lettering--
Includes index.
Keywords: 2 -- 0; 6; Technique.;Technique. -- Architectural drawing;Interior decoration rendering -- 20; 20; 2